Geometrically constrained square pyramidal phosphoranide. Issue 20 (4th May 2022) - Volodarsky, Solomon; Malahov, Irina; Bawari, Deependra; Diab, Mohand; Malik, Naveen; Tumanskii, Boris; Dobrovetsky, Roman
Abstract : Geometrically constrained, square pyramidal phosphoranide was synthesized, and its reactivity study showed that it is both a nucleophile and reductant. Abstract : Geometrical constriction of main group elements leading to a change in the reactivity of these main group centers has recently become an important tool in main group chemistry. A lot of focus on using this modern method is dedicated to group 15 elements and especially to phosphorus. In this work, we present the synthesis, isolation and preliminary reactivity study of the geometrically constrained, square pyramidal (SP) phosphoranide anion (1 − ). Unlike, trigonal bipyramidal (TBP) phosphoranides that were shown to react as nucleophiles while their redox chemistry was not reported, 1 − reacts both as a nucleophile and reductant. The chemical oxidation of 1 − leads to a P–P dimer (1-1 ) that is formed via the dimerization of unstable SP phosphoranyl radical (1˙ ), an unprecedented decay pathway for phosphoranyl radicals. Reaction of 1 − with benzophenone leads via a single electron transfer (SET) to 1-OK and corresponding tetraphenyl epoxide (4 ).